Validation Study of Histamine Test for the Determination of Histamine in Selected Fish Products. (23rd November 2019) - Shimoji, Kazuhiko; Bakke, Mikio; Hungerford, James M; Mireles DeWitt, Christina A; Köse, Sevim
Abstract: Background: Since prescribed limits for histamine in fish have been set by various regulatory bodies around the world, the rapid, specific and easy determination of histamine is in high demand. Objective: The enzymatic histamine assay developed by Kikkoman Biochemifa Co. was validated. Methods: Fresh and frozen raw tuna, canned tuna in oil and water, and anchovy fish sauce were used for the validation study under the specific guidelines of the AOAC Research Institute Performance Tested Method SM (PTM) program. Results: Good linearity (R 2 > 0.9997) for histamine standard solutions, recovery rates (90.3–125.2%), and repeatability precisions (RSDr < 10%) were shown for all spiked tested matrixes. The claimed LOQ values, 20 and 10 mg/kg for solid fish and 160 and 80 mg/kg for fish sauce using a 1 and 2 cm optical path length spectrophotometer, respectively, were validated. The cross-reactivity test showed no positive interference of other biogenic amines, except for agmatine and putrescine. Moreover, no inhibition was confirmed among the 12 biogenic amines. Stability data supported the shelf life (42 months at 4°C), lot-to-lot consistency was demonstrated, and the method was shown to be robust. Independent laboratory testing using canned tuna in oil demonstrated that the recovery ranged from 93.5 to 124.7%, and the RSDr at all spike levels was <20%. Conclusions: The simple and rapid enzymatic histamine assay method has been successfully validated. Highlights: This histamine quantitative assay kit was qualified for PTM certification No. 041802.